Evaluation of production efficiencies among primiparous suckler cows of diverse genetic index at pasture. (3rd October 2017) - McCabe, S.; McHugh, N.; Prendiville, R.
Abstract : This study aimed to determine estimates of production efficiency among primiparous suckler cows of diverse genetic merit (GM) for the national Irish maternal index. Data from 82 heifers of diverse GM across two different replacement strategies (suckler (S) or dairy (D) sourced) were available. Milk yield, grass dry matter intake, cow BW and body condition score (BCS) were recorded. The maternal index had no significant effect on any parameters investigated, whereas S cows were 86 kg heavier in BW, had a 0.33 greater BCS and 0.6 UFL greater NEM requirement compared with D beef crossbred (F1 ) cows. The F1 produced 2.2 kg/day more milk and had greater lactation energy requirements (0.8 UFL) than S. The F1 produced 0.48 kg milk per 100 kg BW and 0.15 kg more milk per unit intake. An interaction between GM and cow origin (CO) showed that F1 low merit cows consumed an additional 1 kg DM than F1 high, and that S high merit cows produced 1.5 kg less milk than their S low counterparts resulting in a 0.5 UFL greater energy requirement for milk production for S low. The F1 high merit cows produced 0.12 kg more milk per unit intake than F1 low cows, whereas S low cows produced 0.12 kg less milk per unit intake than S high. The F1 low cows consumed 0.17 kg more DM per unit BW than F1 high. Thus, genetic selection for maternal traits has not resulted in differences in production efficiency traits, however CO differences were observed.